An environmentally stable supramolecular biosolvent: Characterization and study of its potential for the elimination of polar toxic substances in water. (25th October 2021) - Romera-García, Encarnación; Ballesteros-Gómez, Ana; Rubio, Soledad
Abstract: Supramolecular solvents (SUPRASs), which are nanostructured liquids made up of non-covalent self-assembled amphiphilic aggregates, are highly promising for the development of engineered green solutions for elimination/reduction of toxic substances in water. However, the reversible and dynamic character of these aggregates have so far prevented the development of cost-effective and scalable strategies. Here, bioSUPRASs made up of non-dynamic assemblies were synthesized from the acid-induced coacervation of rhamnolipids (RLs). These bioamphiphiles contain multiple –COOH and –OH groups, which resulted in RL assemblies with a high intermolecular cohesive force. The synthesis occurred spontaneously, at concentrations of hydrochloric acid as low as 0.01 M, and it took place with high atom-economy (more than 99% of the RL was incorporated into the bioSUPRAS) and under energy-saving conditions (e.g. room temperature). The bioSUPRAS, made up of RL (80 ± 4%, w/w) and water (27 ± 2%, w/w), was environmentally stable, which allowed their direct application to water bodies. This feature, along with the high concentration of RL in the bioSUPRAS (∼840 g L −1 ) and the mixed-mode mechanisms offered for solute solubilisation, enabled its application to the efficient extraction of highly water-soluble toxic substances (recoveries for ionic dyes were in the range ∼70–100% at fractional bioSUPRAS phase volumes between 0.008 and 0.018). This research shows that highly stable bioSUPRASs can be produced by proper selection of amphiphiles, which should enable the eco-efficient and cost-effective elimination of toxic substances from water bodies. Graphical abstract: Image 1 Highlights: A rhamnolipid-based supramolecular biosolvent is synthesized and characterized. The bioSUPRAS is made up of irreversible and non-dynamic self-assembled aggregates. The bioSUPRAS remains stable in contact with large water volumes. Its potential for the elimination of highly water soluble toxic substances is proved. BioSUPRAS constitutes an engineered green alternative to petroleum-derived solvents.